Widespread and progressive brain atrophy is a common feature in patients with mitochondrial disease - Mickelsson, Nora; Hirvonen, Jussi; Martikainen, Mika H. (Springer Nature, 2026)
Background
Primary mitochondrial diseases comprise a group of inherited disorders that frequently affect the central nervous system. Previous studies have reported brain imaging findings commonly associated with mitochondrial disease. However, longitudinal data on volumetric brain abnormalities, their progression in time, and associations with clinical features of the disease remain limited.
Methods
We conducted a retrospective observational study of 36 patients with genetically confirmed mitochondrial disease at Turku University Hospital (Turku, Finland). A total of 73 brain magnetic resonance scans (1–8 per patient) were analysed using the cNeuro® image quantification tool to assess lobar and regional cortical atrophy. Associations with clinical features, including stroke-like episodes (SLEs), sex, and genetic subtype, were investigated.
Results
Cerebral atrophy was present in all patients and was most pronounced in the temporal and occipital lobes. Patients with a history of SLEs exhibited significantly greater atrophy in both temporal lobes and the right occipital and parietal lobes. Follow-up imaging (available for 15 patients) revealed progressive atrophy, particularly in the occipital lobes, in patients with SLEs. No significant differences in atrophy severity or progression were found between patients with the m.3243A > G variant and those with other genetic causes.
Conclusions
Cerebral atrophy is a common and often progressive feature of mitochondrial disease, even in patients without clinical brain symptoms. Atrophy predominantly affects posterior brain regions, and its progression is particularly evident in patients with SLEs. These findings underline the neurodegenerative nature of mitochondrial disease and highlight the need to develop neuroprotective therapies.